Social balance of cooperatives and social enterprises: Cooperativa de Consumo El Grullo in Jalisco case - Aguilar Hernández, Eduardo Enrique (Cooperativismo & Desarrollo, 2017)
Purpose: The present work is framed within the joint project of four Mexican universities that aim to create an evaluation system for the social area of cooperatives and social enterprises. Description: The evaluation is carried out applying several instruments found in the Manual of Administrative Procedures that evaluate the cooperative principles established by the International Cooperative Alliance. Point of view: This paper presents the results of the application of the Manual of Administrative Procedures’ instruments to the Cooperativa de Consumo El Grullo, located in the south of Jalisco, Mexico. Conclusions: The analysis offers insight about the strengths and weaknesses of the social action of the cooperative with the objective of generating lessons for the other entities of the solidarity economy. The instruments presented in the Manual of Administrative Procedures constitute useful tools that allow the generation of indicators for later analysis. The results of the Manual of Administrative Procedures’ application offer a guideline to follow, however, it should be clarified that these principles must be articulated with the cooperative’s established mission.